Perancangan UI/UX Game Environment Crime Case - Nugroho Ridho Harjanto; Riyan Abdul Aziz; Indrawan Ady Saputro (Pusat Riset dan Inovasi Nasional, 2024)
A game is a game that aims to entertain and has an implicit meaning in it. A person can get entertainment by playing games as a medium of entertainment. This environment criminal case game presents a game with the theme of environmental damage with a casual genre of investigating the causes of environmental damage. With the presence of this game, it is hoped that players will understand the implied meaning so that they can participate in protecting the environment in accordance with the theme of this game. The method used is design thinking with five stages, namely Empethize, Define, Idea, Prototype and Test.